(untitled) (Plant Tissue Culture and Biotechnology, 2019)
Embryogenic callus was obtained from the leaf explants of jojoba (Simmondsia chinensis (Link) Schneider cultured on MS containing 0.5 mg/l NAA and 0.5 mg/l Kn. Growth of embryonic callus increased in 0.5 mg/l Kn + 6% sucrose. In order to improve oil content, the embryonic callus was exposed to different doses (5, 10 and 15 Kr) of gamma radiation. It was found that oil content of embryonic callus of jojoba increased 1.41% by exposing to 5 Kr gamma radiation. Also, size of oil bodies in embryonic callus irradiated with 5 Kr increased compared to control. Furthermore, production of the fatty acids was enhanced by gamma irradiation. The highest percentage of total fixed oil (1.41) was recorded in 5 Kr radiation. However, the highest content of total fatty acids (98.612) was obtained when embryonic callus were exposed to 10 Kr of gamma radiation.